2021
DOI: 10.3390/ijms222413311
|View full text |Cite
|
Sign up to set email alerts
|

Immune Regulatory Processes of the Tumor Microenvironment under Malignant Conditions

Abstract: The tumor microenvironment (TME) is a critical regulator of tumor growth, progression, and metastasis. Since immune cells represent a large fraction of the TME, they play a key role in mediating pro- and anti-tumor immune responses. Immune escape, which suppresses anti-tumor immunity, enables tumor cells to maintain their proliferation and growth. Numerous mechanisms, which have been intensively studied in recent years, are involved in this process, and based on these findings, novel immunotherapies have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 461 publications
(464 reference statements)
0
43
0
Order By: Relevance
“…To further grasp the extent of immune infiltration between the two groups, we used ESTIMATE, CIBERSORT, and ssGSEA, which suggested that the tumor immune response in group 1 may be more active than group 2. TME consists of more than 30 different tumor-infiltrating non-malignant cell types, as well as ECM, which both promote tumorigenesis and play key roles in anti-tumor immune responses [ 43 ]. Tumor-associated macrophages (TAMs) are the main component of TME, and have a vital function in the proliferation, invasion and metastasis of tumor cells and the inhibition of T cells anti-tumor immune response.…”
Section: Discussionmentioning
confidence: 99%
“…To further grasp the extent of immune infiltration between the two groups, we used ESTIMATE, CIBERSORT, and ssGSEA, which suggested that the tumor immune response in group 1 may be more active than group 2. TME consists of more than 30 different tumor-infiltrating non-malignant cell types, as well as ECM, which both promote tumorigenesis and play key roles in anti-tumor immune responses [ 43 ]. Tumor-associated macrophages (TAMs) are the main component of TME, and have a vital function in the proliferation, invasion and metastasis of tumor cells and the inhibition of T cells anti-tumor immune response.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor microenvironment (TME) is the cellular environment influencing the process of tumors and is composed of immune cells (both innate and acquired immune cells), nonimmune stromal cells (such as fibroblasts, endothelial cells, and various tissue-associated cells), and extracellular matrix proteins ( Monteran and Erez, 2019 ; Wculek et al, 2020 ; Pansy et al, 2021 ). Among them, all kinds of cells interact with each other and cancer cells through the secretion of various cytokines, chemokines, and other signals, so they play a key role in the regulation of the tumor immune response.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor microenvironment (TME) is the local ecological environment on which tumor cells depend, and it includes immune cells, endothelial cells, microvasculature, and cytokines [ 20 ]. The interaction between the tumor and the immune cells undergoes a remodelling of the immune system, and eventually, tumor cells use a series of mechanisms to undergo immune escape or tumor dormancy.…”
Section: Introductionmentioning
confidence: 99%